1999
DOI: 10.1021/jp990278h
|View full text |Cite
|
Sign up to set email alerts
|

On the Micellar Aggregates of Alkali Metal Salts of Deoxycholic Acid

Abstract: The X-ray patterns of lithium (LiDC) and potassium (KDC) deoxycholate fibers, drawn from aqueous micellar solutions, have been interpreted by means of a packing of 8/1 helices formed by trimers. Previously, these helices satisfactorily represented the structure of the sodium (NaDC) and rubidium (RbDC) deoxycholate micellar aggregates. Dielectric measurements show that the trend of the average electric dipole moment µ of a NaDC monomer as a function of temperature and concentration supports a two-structure equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…Structural studies showed that helical models described satisfactorily aqueous solutions of micellar aggregates of dihydroxycholanic salts (DC, GDC, TDC). [12][13][14] The hypothesis can be formulated that GDC increases along a cylinder and GC tends to block the increasing of the helical of GDC by positioning at the two bases of the cylinder. On the other side, aggregation numbers of GC are smaller than 24 (value observed in solutions where GC was the alone bile salt), because it is probable that the excess of GC increases the percentage of monomer or dimer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies showed that helical models described satisfactorily aqueous solutions of micellar aggregates of dihydroxycholanic salts (DC, GDC, TDC). [12][13][14] The hypothesis can be formulated that GDC increases along a cylinder and GC tends to block the increasing of the helical of GDC by positioning at the two bases of the cylinder. On the other side, aggregation numbers of GC are smaller than 24 (value observed in solutions where GC was the alone bile salt), because it is probable that the excess of GC increases the percentage of monomer or dimer.…”
Section: Resultsmentioning
confidence: 99%
“…2 -16 Earlier investigations carried out on solutions of sodium salts of dihydroxycholanic (deoxycholate and its conjugates) 17 -19 and trihydroxycholanic (cholate and its conjugates) 14,[20][21][22] showed a very different behaviour with regard to the aggregation number, the participation of hydrogen ions to the aggregate formation and the basic unit constituent of the micelles of the two kinds of cholanic salts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…were studied by many researchers. [4][5][6][7][8][9][10][11][12][13][14][15][16] The results obtained from e.m.f. measurements, carried out as a function of hydrogen ions, reagents and ionic medium 17 concentrations on aqueous sodium salt solution of dihydroxycholanic acids (deoxycholate = NaDC 18 , glycodeoxycholate = NaGDC 19 and taurodeoxycholate = NaTDC 20 ), were explained by assuming the presence of several species with different odd high aggregation numbers and also formed with the uptake of protons.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Prevailing aggregation numbers, stability of the formed species and their range of existence were studied in aqueous solutions by means of electromotive force (e.m.f.) measurements as a function of hydrogen ion and reagent concentration.…”
Section: Introductionmentioning
confidence: 99%